What Explains Vietnam's Exceptional Performance in Education Relative to Other Countries? Analysis of the 2012 and 2015 Pisa Data - Hai-Anh Dang; Paul Glewwe; Khoa Vu; Jongwook Lee (Institute of Labor Economics (IZA), 2021)
Despite being the poorest or second poorest participant, Vietnam performed much better than all other developing countries, and even ahead of wealthier countries such as the U.S. and the U.K., on the 2012 and 2015 PISA assessments. We provide a rigorous investigation of Vietnam's strong performance. After making various parametric and non-parametric corrections for potentially non-representative PISA samples, including bias due to Vietnam's large out-of-school population, Vietnam still remains a large positive outlier conditional on its income. Possible higher motivation of, and coaching given to, Vietnamese students only partly explains Vietnam's performance, and this is also the case for various observed household- and school-level variables. Finally, Blinder-Oaxaca decompositions indicate that the gap in average test scores between Vietnam and the other participating countries is due not to differences in students' and schools' observed characteristics, but instead to Vietnam's greater "productivity" of those characteristics.
Keywords: H0; I2; O1; P3; 330; education; student learning; test scores; enrollment; PISA; Vietnam